Application of response surface methodology to optimize chromium (VI) removal from aqueous solution by cassava sludge-based activated carbon. Issue 1 (February 2021) - Guo, Changjin; Ding, Lei; Jin, Xiaopeng; Zhang, Huiwen; Zhang, Dewei
Graphical abstract: Highlights: A new activated carbon (CSAC) from cassava sludge was prepared and characterized. Operating parameters for Cr(VI) removal were optimized by RSM based on BBD. Optimum states: 4.23 mg L-1 concentration, 1.48 g l -1 dosage, 34.87 min, pH 4.11. Maximum Cr(VI) removal efficiency of 99.04 % predictably and 98.22 % experimentally. The prepared CSAC showed excellent reusability during 4 cycles. Abstract: This study aimed at optimizing the hexavalent chromium (Cr(VI)) removal from aqueous solution by a new cassava sludge-based activated carbon (CSAC) using response surface methodology involving Box-Behnken Design. The CSAC was characterized by field emission scanning electron microscopy, Brunauer-Emmett-Teller, N2 adsorption-desorption isotherms measurements, Fourier transform infrared, X-ray diffraction, and zeta potential. The effects of four significant variables including initial Cr(VI) concentration, CSAC dosage, adsorption time and pH, were optimized by a quadratic model. The results were proved to be reliable by analysis of variance. The Pareto analysis indicated that pH had the greatest influence on the Cr(VI) removal among the four selected variables. The optimum parameters for Cr(VI) removal were found to be 4.23 mg L −1 initial Cr(VI) concentration, 1.48 g L -1 CSAC dosage, 34.87 min adsorption time, and solution pH 4.11. The predicted Cr(VI) removal efficiency of 99.04 % is in good agreement with the experimental result of 98.22 % at optimum conditions. The regeneration results indicated that the removal efficiency of Cr(VI) still maintained 74.91 % after four repeated adsorption-desorption cycles. Therefore, CSAC can be considered as a potential adsorbent for efficient and rapid adsorption of Cr(VI) from water.